Exploring the graduates’ perception of English language materials in Vocational High Schools - A. Wiqoyil Islama; Dzulfikri Dzulfikri; Wardatun Nadzifah (Universitas Merdeka Malang, 2022)
Instead of continuing their studies, Vocational High School (SMK) students are prepared to work following graduation. Thus, instead of using general English, ESP (English for Specific Purposes) should be integrated in SMK. However, the Indonesian National Curriculum decided to teach both SMA (General High School) and SMK the same general English content. The purpose of this study is to see how graduates feel about the EFL materials they received at SMK. This research involved three SMK graduates as participants. This investigation yielded three recommendations. First, ESP resources should be incorporated to the English topic in SMK without omitting the need for general English materials. Second, SMK classroom activities should place a greater emphasis on practical communication. Third, extensive reading and/or listening activities should be implemented in SMK.DOI: 10.26905/enjourme.v7i1.7445